Static Analysis of the Effect of Shape Memory Alloy in Laminated Beam - et. al., Radha Tomar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study deals with the effect of shape memory alloy in carbon/epoxy laminated beam. In this study we analyses static response of laminated beam under the load of 10 KN at the mid span of the beam. In this study a cantilevered beam of dimension 1000mm length, 100mm width and 30mm height which is divided in 3 layers of 10mm each is considered. The study includes three cases. In first case all the 3 layers of beam is laminated with carbon/epoxy. In second case the top and the bottom layers are laminated with carbon/epoxy and middle layer is2qw laminated with shape memory alloy. In the third case the top and the bottom layers are laminated with shape memory alloy while the middle with carbon/epoxy. Loading and boundary conditions are same for all the three cases. All the analysis is done using ANSYS workbench 15.0